The Anthropocene as rupture. (August 2016) - Hamilton, Clive
I argue that Earth System science – a recent paradigm shift in the earth and life sciences (Hamilton C and Grinevald J (2015) Was the Anthropocene anticipated? The Anthropocene Review 2(1): 59–72) – named the Anthropocene as the very recent rupture in Earth history arising from the impact of human activity on the Earth System as a whole. Many have mistakenly treated the new concept of the Earth System as if it were equivalent to 'the landscape', 'ecosystems' or 'the environment'. The new paradigm of Earth System science is erroneously understood as no more than a variation or development of established ecological sciences. Various attempts to invent new starting dates for the new epoch are based on these misconceptions, as are a number of arguments deployed to reject the Anthropocene altogether. In this context I consider the early Anthropocene hypothesis, three readings of the Anthropocene as instances of ecosystem change, and the notion of the 'good Anthropocene'. Using this frame I also assess the arguments of those who do not accept the idea of the new epoch. I defend the view that disciplines other than Earth System science distort the idea of the Anthropocene when they read it through their own lenses.